2017
DOI: 10.1002/2017gl073137
|View full text |Cite
|
Sign up to set email alerts
|

The interplanetary magnetic field observed by Juno enroute to Jupiter

Abstract: The Juno spacecraft was launched on 5 August 2011 and spent nearly 5 years traveling through the inner heliosphere on its way to Jupiter. The Magnetic Field Investigation was powered on shortly after launch and obtained vector measurements of the interplanetary magnetic field (IMF) at sample rates from 1 to 64 samples/second. The evolution of the magnetic field with radial distance from the Sun is compared to similar observations obtained by Voyager 1 and 2 and the Ulysses spacecraft, allowing a comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The typical value of each model input is given in Table . Upstream solar wind inputs are based on published statistics of near‐Jupiter solar wind measurements (Ebert et al, ; Gruesbeck et al, ; Jackman & Arridge, ) and the application of solar wind scaling laws to typical near‐Earth conditions (Slavin & Holzer, ). There are two prevailing IMF directions at Jupiter, depending on whether the heliospheric current sheet is above or below the planet, and these directions are effectively parallel and antiparallel to the y axis (e.g., Jackman & Arridge, ).…”
Section: Typical Conditions At Jupiter's Magnetopause Under Steady Statementioning
confidence: 99%
See 2 more Smart Citations
“…The typical value of each model input is given in Table . Upstream solar wind inputs are based on published statistics of near‐Jupiter solar wind measurements (Ebert et al, ; Gruesbeck et al, ; Jackman & Arridge, ) and the application of solar wind scaling laws to typical near‐Earth conditions (Slavin & Holzer, ). There are two prevailing IMF directions at Jupiter, depending on whether the heliospheric current sheet is above or below the planet, and these directions are effectively parallel and antiparallel to the y axis (e.g., Jackman & Arridge, ).…”
Section: Typical Conditions At Jupiter's Magnetopause Under Steady Statementioning
confidence: 99%
“…Perhaps the most important is the fact that the Jovian magnetosphere is rarely expected to be in steady state, since all model input parameters have either been shown to be or are expected to be functions of time (Ebert et al, ; Frank et al, ; Gruesbeck et al, ; Jackman & Arridge, ; Joy et al, ; Krupp et al, ). Particularly, relevant for magnetopause reconnection is the evidence that the typical time scale of IMF variability at Jupiter's orbit is considerably shorter than both the time taken for the unperturbed solar wind to travel a magnetopause standoff distance (~4 days), as well as the more significant and longer time taken for a change in the IMF immediately upstream of the subsolar bow shock to propagate through the slower magnetosheath flow regime and impact near‐magnetopause conditions (Ebert et al, ; Gruesbeck et al, ; Jackman & Arridge, ; McComas & Bagenal, ). The more realistic picture of large‐scale reconnection at Jupiter's magnetopause is therefore likely one where reconnection sites (X lines) are more mobile in response to relatively rapid changes in the upstream IMF and thus also where the reconnection voltages calculated here may be short‐lived.…”
Section: Assessing the Operation Of Key Processes At Jupiter's Magnetopausementioning
confidence: 99%
See 1 more Smart Citation
“…However, the solar wind does have some effect on the Jovian magnetopause. The magnetic field in the outer Jovian magnetosphere, like its terrestrial counterpart, exhibits temporal and/or spatial variations in both magnitude and direction in response to changes in solar wind dynamic pressure (Acuna et al, 1983) as well as other solar wind properties that vary from 1 to 5 AU and with solar cycle phase (e.g., Gruesbeck et al, 2017). The internal currents, however, do affect the shape and presumably the position as well of the Jovian magnetopause (e.g., Engle & Beard, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Parker 1958;Burlaga et al 1984). Gruesbeck et al (2017) found that applying the expected 1/r relationship to the Juno cruise data resulted in a very good fit to the magnetic field data. The magnetic field strength throughout the cruise phase was also found to be of lower magnitude in comparison to observations of previous solar cycles made by Voyager and Ulysses.…”
Section: Overview Of Juno Cruise Datamentioning
confidence: 94%